Sejarah Toponimi Dusun “Talun” Desa Kenjo Kecamatan Glagah Kabupaten Banyuwangi melalui Tuturan Tradisi Lisan - Novita Sari; Hervina Nurullita (CV Cendekia Paramartha, 2026)
This study aims to reconstruct the toponymic history of Talun Hamlet in Kenjo Village, Glagah Subdistrict, Banyuwangi Regency, through the community’s oral traditions, and to analyze the historical and cultural meanings embedded within them. The study employs a qualitative approach using an oral history design combined with toponymic analysis. Data were collected through in-depth interviews with community leaders, village elders, and residents knowledgeable about local history, supplemented by field observations and documentary research. Data analysis involved data reduction, data presentation, historical interpretation, and drawing conclusions through source triangulation to ensure the validity of the findings. The results of the study indicate that the toponymy of Talun emerged from the community’s interaction with the geographical environment, the process of settlement migration, and historical experiences passed down across generations through oral tradition. The name Talun not only functions as a territorial marker but also represents the cultural identity, collective memory, and value system of the local community. Oral tradition has proven to play a crucial role in sustaining local historical knowledge while strengthening the community’s historical awareness. This study affirms that toponymy is a vital source for reconstructing local history and preserving the cultural heritage of rural communities.